A Kinematic Estimation of Functional Joint Rotation Centers of Whole Body - Aoki, K.; Kouchi, M.; Mochimaru, M. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
This study is about an estimation method of joint rotation centers. In order to apply motion capture (MoCap) data of the whole body of an actual person to digital manikins or computer graphics models, it is necessary to estimate each rotation center of joint and to define each posture of body segment from the MoCap data. We developed a kinematic estimation method of the functional joint rotation centers and the postures of the whole body. Using the estimation method, a unique model of the subject is made from MoCap data, which are applicable to clinical analysis.